Designing Online Project-based Learning Instruction for EFL Learners: A WebQuest Approach - Chen, Julian (2019)
This action report presents a pedagogically-sound approach to transforming conventional EFL instruction into an active learning environment. Following a constructivist project-based learning (PBL) approach, I propose a WebQuest learning module to demonstrate how EFL teachers can capitalize on cost-effective and user-friendly website builders to create a WebQuest site. Following WebQuest principles, the module includes an introduction of an engaging real-life task, a task procedure, selected online resources for task completion, a project evaluation, and a culmination of student reflection. The synergy of the Internet and the PBL WebQuest optimizes higher-order thinking and problem-solving skills, fosters learner autonomy and motivation, and promotes language use for real-life purposes.